Plastics manufacturing systems engineering a systems approach - Kazmer, David (Hanser Publications, 2009)
"Plastics manufacturing is a highly interdisciplinary endeavor requiring knowledge related to materials science, physics, engineering, and management. This book was written to educate and support plastics processing engineers, but is also highly useful to others involved with plastics manufacturing who are performing process development, research, and even machinery design"--Provided by publisher.
Keywords: Plastics.; Manufacturing processes.; Systems engineering.; elektronické knihy; electronic books